Does the legitimacy of countries influence the internationalization of emerging market multinationals - Ana Plaza-Casado; Alicia Blanco-González; Lourdes Rivero-Gutiérrez; Raúl Gómez Martínez (European Research on Management and Business Economics (ERMBE), 2024)
Legitimacy is fundamental to business internationalization and access to new markets. This variable is particularly important for emerging market multinationals (EMNEs) as they face numerous obstacles, including the information that consumers in the host country have about these companies in addition to the legitimacy of the country of origin. Therefore, this study tests whether home country information and legitimacy affect the legitimacy of EMNEs and consumer purchase intentions. Specifically, this research focuses on EMNEs of Chinese origin due to their rapid growth at the international level and in the fast fashion sector because of the change in the positioning of large brands in favor of sustainability. The model is validated through an empirical study of 261 regular Shein shoppers using PLS-SEM. The academic and managerial implications of this research clarify the antecedents and consequences of the legitimacy of EMNEs and provide recommendations for the management of EMNEs and business success.
Keywords: M16; M31; 650; Country of origin; EMNEs; Internationalization; Legitimacy